Leucena hay apparent digestibility determination by means of different methods - Costa, Emanuel Sousa; de Souza, Antônio Alves; Neto, Francisco Bezerra; Melo Lima, Francisco de Assis; Pereira, Raimundo Mauro Araripe (Pesquisa Agropecuaria Brasileira, 2014)
Leucena (Leucaena leucocephala (Lam) de Wit) hay digestibility was studied by means of different methods to obtain more precise values description, and safe better ration formulation. A trial with entirely randomized blocks, 5 hay levels (0, 25, 50, 75 and 100%), four replications, complemented with corn ear straw was carried out. Twenty castrated males 'Morada Nova' breed sheeps with an average weight of 25 kg were used. Pre-experimental and experimental phases lasted 14 and 7 days, respectively. The combination of hay and corn ear straw resulted in digestibility increase, showing the quadratic effect of the dry matter, energy and crude fiber. A linear effect was found on gross protein digestibility and nitrogen balance. As usual methods for apparent digestibility tests proved to be inadequate is this trial, a method of proportional distribution, that accounts for the increase in digestibility as a consequence of feed association was developed, to estimate dry matter digestibility, crude energy and crude fiber. The methods obtained equivalent results for gross protein digestibility.